Properties of the shallow D-centers in semiconductors with polar and covalent binding - Kashirina, N.I.; Lakhno, V.D.; Sychyov, V.V.; Sheinkman, M.K. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
The theoretical consideration of the energy of the lowest singlet and triplet terms of shallow D¯-centers (two electrons, bound with one-charge Coulomb center) in semiconductors with an ionic and covalent binding has been carried out. The electron-phonon interaction is described by a Frцhlich Hamiltonian. The energy of D¯-center is described with the use of a Buimistrov-Pekar method of canonical transformations for arbitrary electron-phonon coupling. It is shown, that for all area of electron-phonon interaction parameters the Buimistrov-Pekar method yields the lowest values of the ground state energy of D¯-centers and free bipolaron in comparison with the best, for today, numerical calculations of the relevant values which have been carried out within the framework of the direct variation methods. The calculations have shown the lack of the bound metastable triplet states corresponding to the lowest triplet energy term of D¯-center and bipolaron for all the area of electron-phonon interaction parameters, in complete analogy to the Hill theorem about the lack of the bound excited states of H¯ ion. It is shown that the account of interaction with acoustic phonons can produce considerable lowering the ground state energy of D¯-center in comparison with the magnitude 1.0555Ry .